당뇨 환자의 성별에 따른 당화혈색소 검사에 미치는 영향 요인: 지역사회건강조사를 이용하여 - 김윤정(Yun-Jeong Kim); 황병덕(Byung-Deog Hwang) (보건교육건강증진학회지, 2019)
Objectives: In this study, we will study the factors that influence glycated hemoglobin testing by gender. Oh, this study was carried out in order to provide basic data for the development of a health education program on self-management methods for diabetics. Methods: For data analysis, SPSS24.0 was used. Analysis methods were frequency analysis, cross analysis and regression analysis. All analyzes were tested with a significance level of p=.05. Results: Gender, education, household monthly income, subjective health status, treatment method were statistically significant for characteristics of concerning glycated hemoglobin checkup for a year. Education, household monthly income, subjective health status, sleep condition, treatment method were statistically significant for characteristics of concerning glycated hemoglobin checkup for a year of male. Education, household monthly income, treatment method were statistically significant for characteristics of concerning glycated hemoglobin checkup for a year of female. Factors Affecting Glycated Hemoglobin (HbA1c) Checkup of men and women were educational level and treatment method. Conclusions: Therefore, it is necessary to prepare a plan capable of configuring and executing a health education and health promotion program according to the height of the patient's education level during the progress of education for self-management of diabetic patients. KCI Citation Count: 0